CRITICAL REFLECTION AND FEEDBACK FOR MEDICAL STUDENTS: A COMPARATIVE STUDY - Imelda Ritunga; Gandes Retno Rahayu; Yoyo Suhoyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: The physician who reflects critically will interpret the experience, aware of its limitations, and will become life long learner. When implementing reflection learning in medical education, it is necessary to assess the ability of learners to help improve the ability of reflection. The objective of the research is to know the students 'reflection ability by giving feedback and different of reflection ability between intervention group and control group.Method: Research using pre and post control group design. The subjects of the study were 62 students medical students of Faculty of Medicine UGM year II who had collected narrative reflection to Gamel (n = 176 students) and willing to participate, divided into 2 groups with simple random sampling. Intervention of treatment group are giving feedback based on the result of narrative reflection from Gamel followed by narrative reflection assignment. The subjects' narrative reflection was assessed using the REFLECT rubric, and analyzed by Wilcoxon and Mann-Whitney tests.Results: The results showed that students' pre and post test reflection ability is in the reflection stage. Giving feedback once does not increase the ability from  reflection stage to the critical reflection stage. This result may be due to several things: critical reflection does not occur without significant / dramatic experience that shifts perspective resulting in transformative learning, feedback is given regularly, lack of trustworhty to instructors who are not university lecturers. Another result of a decrease in the ability of reflection in general after 6 months indicates the need to do reflection activity / assignment in each semester to maintain and improve the ability of reflection. Conclusion: Increased reflection ability from reflection stage to critical reflection stage does not occur with single feedback. If reflection is not done regularly, it can cause a decrease in reflection ability.